Pengaruh Arus Kas Operasi dan Pertumbuhan Penjualan terhadap Tax Avoidance dengan Intensitas Modal Sebagai Variabel Moderasi - Safitri, Aurora; Muanifah, Suciati (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
This study aims to examine several variables that influence tax avoidance, namely operating cash flow and sales growth and using a moderating variable of capital intensity. The sample for this research is Energy companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Using a purposive sampling method with a population of 74 companies and a research sample of 6 companies with observations for 5 (five) years, namely the period 2017 – 2021. The research results prove that (1) operating cash flow and sales growth have a simultaneous effect on tax avoidance. (2) operating cash flow has no significant effect on tax avoidance. (3) sales growth has no effect on tax avoidance (4) capital intensity weakens the relationship of operating cash flow to tax avoidance (5) capital intensity weakens the relationship of sales growth to tax avoidance